PERBEDAAN HASIL LAJU ENDAP DARAH METODE WESTERGREN PADA DARAH ETHYLENE DIAMINE TETRA-ACETIC ACID MENGGUNAKAN DILUEN NATRIUM SITRAT DENGAN NATRIUM KLORIDA - I Gusti Agung Dewi Sarihati; I Gusti Ngurah Teja Pratama; Cok Dewi Widhya HS; Heri Setiyo Bekti (Meditory : The Journal of Medical Laboratory, 2019)
Background: Erythrocyte sedimentation rate is a hematological parameter that measures sedimentation speed of erythrocytes in the blood with anticoagulants placed vertically on a standard pipette for one hour and expressed in mm / hour. One factors that influence the erythrocyte sedimentation rate is dilution factor. Purposed: This study was intended to determine the difference of Westergren blood erythrocyte sedimentation rate in EDTA blood using diluent sodium citrate 3.8% and 0.85% NaCl.Method: This research is an experiment with a posttest only control group design. The erythrocyte sedimentation rate was carried out by the Westergren method on 30 EDTA blood samples. The control group used diluen NaCl 0.85% and the treatment group used diluent sodium citrate 3.8%.Result: The average erythrocyte sedimentation rate using a NaCl 0.85% solution is 19.77 mm/hour while the erythrocyte sedimentation rate using diluent sodium citrate 3.8% solution 17.53 mm/hour. Independent sample T-test obtained pɑ (0.05) means that there was no difference in Westergren erythrocyte sedimentation rate results in EDTA anticoagulants using diluent sodium citrate 3.8% and NaCl 0.85%.Conclusion: Sodium citrate 3.8%  can be considered to be diluted for EDTA blood for examination of the Westergren method erythrocyte sedimentation rate in addition to  NaCl 0.85%. Keywords: Erythrocyte Sedimentation rate; Westergren method; EDTA blood; Sodium citrate 3.85; NaCl 0.85%.